2013
DOI: 10.1111/j.1750-3841.2012.03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Antioxidant Activity of Physiological Drop of Citrus Fruits

Abstract: Physiological drop of citrus fruits may be a good resource of bioactive compounds including flavonoids, phenolic acids, limonoids, synephrine, and a good material of nutraceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 27 publications
8
56
2
3
Order By: Relevance
“…Without any doubt, hesperidin, present in most of the Citrus extracts screened in the HPTLC analysis, could be one of the compounds contributing somewhat to BChE inhibitory eff ects of the extracts. Caff eic acid, a dominant phenolic compound available in many Citrus cultivars (25,26), was reported earlier to exhibit either low inhibitory activity ((11.05±1.03) % at 100 μg/mL) against AChE (27) and IC 50 ≥200 μM (28) or no inhibition (29), which is consistent with our result ((6.01±2.50) % at 100 μg/mL).…”
Section: Hptlc Profi Le Of the Extractssupporting
confidence: 82%
“…Without any doubt, hesperidin, present in most of the Citrus extracts screened in the HPTLC analysis, could be one of the compounds contributing somewhat to BChE inhibitory eff ects of the extracts. Caff eic acid, a dominant phenolic compound available in many Citrus cultivars (25,26), was reported earlier to exhibit either low inhibitory activity ((11.05±1.03) % at 100 μg/mL) against AChE (27) and IC 50 ≥200 μM (28) or no inhibition (29), which is consistent with our result ((6.01±2.50) % at 100 μg/mL).…”
Section: Hptlc Profi Le Of the Extractssupporting
confidence: 82%
“…Foyou, while nobiletin and tangeretin were the dominant PMFs in C. paradise cv. Huyou (Sun et al 2013), which was similar with pummelo and grapefruit (Xi et al 2014a(Xi et al , 2015. Nobiletin was the most abundant PMFs in lemon, it ranged from nd to 107.3 lg/g FW, which was significantly higher than the contents reported in wild mandarin and grapefruit (Xi et al 2015;Zhang et al 2014), except for peels, lemon whole fruit, pulp and juice were also good source of sinensetin, nobiletin and tangeretin.…”
Section: Individual Phenolic Compound Contentsmentioning
confidence: 56%
“…Three flavanones; naringin, hesperidin and narirutin were identified in both varieties. However, studies done by Sun et al (2013) and Robards et al (1997) on pummelo showed that only naringin and tangeretin were present. Whereas, grapefruit compounds studied by Robards et al (1997) showed hesperidin and narirutin were present, the exact compounds found in this study on both varieties.…”
Section: Flavanonesmentioning
confidence: 99%
“…Both enzymatically clarified juices, have shown a slight decrease (p >0.05) of total phenolic contents for both varieties. This slight difference might be due to a number of reasons; (1) Temperature of enzymatic clarification treatment ( Table 1): temperature that was used was not high enough to warrant an optimum enzymatic reactivity which was reported (Sun et al 2013) in the range of 50°C. The author also noted that the pH of the juice during the clarification treatment played an important role, where the optimum pH was found to be 5.8. pH and both varieties of pummelo fruit juice was kept at 4.0 to maintain the acidity level of the juice.…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%